High-temperature-resistant fluoride-free waterproof breathable nanofiber membrane and preparation method thereof
Through electrospinning technology and pre-oxidation treatment, high temperature resistant, fluorine-free, waterproof and breathable nanofiber membranes were prepared, solving the problems of complex preparation, high energy consumption and harmful materials in the prior art, and achieving a high-performance and environmentally friendly waterproof and breathable membrane.
Patent Information
- Application Number
- CN202510001511.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-08
AI Technical Summary
In the preparation technology, the existing waterproof and breathable membranes have problems such as complex forming mechanism, obvious thermodynamic phase diagram division, difficult to control interaction parameters, uneven pore size distribution, low water pressure resistance, high energy consumption, large equipment footprint, and technology monopolized by foreign companies. At the same time, perfluoro and polyfluoroalkyl substances are harmful to the environment and the human body.
The silicon-based acrylonitrile terpolymer was synthesized by electrospinning technology and combined with a hydrophobic modifier. The nanofiber membrane was prepared by electrospinning and pre-oxidation treatment was performed to form a ketone carbonyl structure, achieving high temperature resistance, fluorine-free, waterproof and breathable functions.
The prepared nanofiber membrane has high contact angle, good moisture permeability, high hydrostatic pressure, excellent waterproof and breathable properties and mechanical properties. It is also green and environmentally friendly, and is harmless to the human body and the environment.
Smart Images

Figure CN119777071A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrostatic spinning functional materials, and specifically relates to a high-temperature resistant, fluorine-free, waterproof and breathable nanofiber membrane and a preparation method thereof. Background Art
[0002] Waterproof breathable materials are intelligent functional materials that have the functions of blocking liquid water penetration and intrusion and transporting and conducting water vapor. Its waterproof performance can meet the needs of daily life and special use requirements. At the same time, the breathability and moisture permeability improve the comfort of the material, and it has more characteristics and advantages of intelligent materials. Therefore, it is also called "breathable fabric" and is widely used in textiles and clothing, medical and health care, construction, filtration and separation, electronics and electrical engineering, seawater desalination and other fields. At present, high-performance waterproof and breathable membrane products mainly come from international brands (such as Gore-Tex, eVent, The North Face, Sympatex, etc.), which leads to the lack of voice of domestic brands in core technology. Therefore, it is of great significance to develop highly waterproof and highly moisture permeable / breathable waterproof and breathable membranes.
[0003] There are three main strategies for the preparation of hydrophobic microporous membranes: (1) using phase separation technology to prepare microporous films with interconnected pores; (2) using flash evaporation to prepare fiber nonwovens; (3) using biaxial stretching technology to prepare polytetrafluoroethylene (PTFE) membranes with small pore structures (average pore size <0.2 μm). These prepared materials have good moisture permeability and significantly enhanced waterproofness, but there are still huge challenges in preparation technology, such as the complex molding mechanism involved, the requirement for a clear boundary in the thermodynamic phase diagram, the difficulty in controlling the interaction parameters, the uneven distribution of the pore size of the prepared membrane, the non-through-structure of the membrane pores, and the low porosity; the coarse fiber diameter and large pore size result in low water pressure resistance; the preparation process needs to always maintain >200 o C, and continuous stretching in two perpendicular directions at the same time, there are problems such as high energy consumption, large equipment footprint, low controllability of membrane structure, and the technology is monopolized by foreign companies. Compared with the above technologies, electrospinning technology can produce nanofiber membrane materials with small fiber diameter and pore size between fibers, high interfiber porosity, large material specific surface area, and adjustable surface structure. At the same time, electrospinning technology has the advantages of strong operability, strong process adjustability, and great industrialization potential. It has become a simple and effective method for preparing superhydrophobic microporous nanofiber membranes. However, waterproof and breathable nanofiber membranes still face huge challenges in large-scale preparation and further improvement of physical and chemical stability.
[0004] In addition, in the development of many waterproof and breathable membranes, perfluorinated and polyfluoroalkyl substances (PFAS, permanent chemicals that take a long time to decompose in the natural environment) have been widely used. These substances can accumulate in the environment and the human body. Organizations such as the United Nations, OECD, HBM4EU, the European Economic Area and the Environmental Protection Agency have emphasized the harm of these PFAS pollutants to the environment and the human body. Therefore, it is urgent to develop high-performance environmentally friendly waterproof and breathable membranes. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a high temperature resistant, fluorine-free, waterproof and breathable nanofiber membrane and a preparation method thereof. The membrane is waterproof, breathable, and high temperature resistant, and is green and environmentally friendly and has no harm to the human body and the environment.
[0006] The present invention provides a high temperature resistant, fluorine-free, waterproof and breathable nanofiber membrane, wherein the contact angle of the nanofiber membrane is greater than 130° and less than 170°, the pore size is 100-1000 nm, the porosity is 50-95%, and the elasticity is 50-200%.
[0007] Compared with the prior art, the nanofiber membrane of the present invention has high hydrophilicity and hydrophobicity. Since the hydrophobic, high temperature resistant, fluorine-free, waterproof and breathable nanofiber membrane has a higher contact angle, it effectively increases the intrusion of external liquid water and ensures the long-term moisture permeability of the nanofiber membrane.
[0008] In some embodiments, the hydrostatic pressure of the nanofiber membrane is 50-150 kPa, the air permeability is 1-20 mm / s, and the moisture permeability is 1-10 4 g / (m 2 24 h), and the waterproof level is >4.
[0009] Compared with the prior art, the nanofiber membrane of the present invention is structurally a high-temperature resistant, fluorine-free, waterproof, breathable nanofiber membrane composed of randomly stacked nanofibers, with small pore size (100 nm-1000 nm), high porosity (50%-95%), good pore connectivity, and the pore structure can be effectively controlled by adjusting the fiber diameter, stacking density, etc. A large number of interconnected microporous channels can effectively prevent the penetration of liquid water and quickly transfer water vapor. At the same time, the welding points between the nanofibers increase the mechanical properties of the high-temperature resistant, fluorine-free, waterproof, breathable nanofiber membrane.
[0010] The second object of the present invention is to provide a method for preparing a nanofiber membrane, the preparation method specifically comprising the following steps: S1. Synthesis of silicon-based acrylonitrile terpolymer: mixing raw materials to obtain a mixed reaction system, placing the mixed reaction system under a nitrogen atmosphere, and performing a free radical polymerization reaction under stirring to obtain a silicon-based acrylonitrile terpolymer; S2, preparing an electrospinning solution: dissolving the silicon-based acrylonitrile terpolymer obtained in step S1 and a hydrophobic modifier in an organic solvent to obtain an electrospinning solution; S3, preparing a semi-finished nanofiber membrane: using the electrospinning solution prepared in step S2 as a raw material, an electrospinning method is used to prepare a semi-finished nanofiber membrane; S4, pre-oxidizing the semi-finished nanofiber membrane obtained in step S3 to cyclize the silicon-based acrylonitrile terpolymer to form a ketocarbonyl structure, thereby obtaining a high-temperature resistant, fluorine-free, waterproof and breathable nanofiber membrane.
[0011] Compared with the prior art, the preparation method of the present invention achieves high temperature resistance, fluorine-free waterproof and breathable functional properties by synthesizing silicon-based acrylonitrile terpolymers and combining hydrophobic modifiers with electrospinning technology. Free radical polymerization is carried out under nitrogen protection to ensure the output of high-quality materials, while pre-oxidation treatment enhances the stability and functionality of the materials. The nanofiber modification process does not involve chemical substances such as PFOS (perfluorooctane sulfonyl compounds) and PFOA (perfluorooctanoic acid), effectively ensuring human health and the ecological environment; in addition, its highly customizable characteristics allow performance parameters to be flexibly adjusted according to specific application scenarios, thereby meeting diverse needs, showing significant technological innovation and cost-effectiveness advantages.
[0012] In some embodiments, in step S1, the raw materials are composed of an initiator, acrylonitrile, a double-bond silane monomer, a double-bond amide monomer and a solvent, and the molar ratio of the acrylonitrile, the double-bond silane monomer and the double-bond amide monomer is (5-20): (0.5-10): (10-30), the mass of the initiator is 0.1-1% of the mass of acrylonitrile, and the concentration of the mixed reaction system is 5-60%.
[0013] Compared with the prior art, the present invention adopts the above raw materials to prepare a mixed reaction system, wherein the molar ratio of acrylonitrile, double-bond silane monomer and double-bond amide monomer is set to (5-20): (0.5-10): (10-30). This ratio ensures that the monomers can be free radical polymerized in an optimal manner. The mass of the initiator is only 0.1-1% of the mass of acrylonitrile. This range can ensure sufficient active centers to start the polymerization reaction, and will not produce unnecessary side reactions or reduce the molecular weight due to excessive initiator. The polymerization reaction is carried out under nitrogen protection, which effectively prevents interference from oxygen and other impurities, reduces the occurrence of side reactions, and reduces the generation of harmful by-products. The realization of fluorine-free waterproof and breathable properties reduces the use of environmentally harmful substances, which is beneficial to environmental protection and sustainable development goals.
[0014] In some embodiments, in step S1, the initiator is selected from at least one of benzoyl peroxide, tert-butyl peroxide, diisopropyl peroxide, potassium permanganate, ammonium persulfate, and azobisisobutyronitrile, and the double-bond silane monomer is selected from vinyl triethoxysilane, vinyl trimethoxysilane, dimethylethoxy vinyl silane, butyl triethoxysilane, 2,6-octadienyl triethoxysilane, cis-2-butenyl triethoxysilane, 2-(3-cyclohexenylethyl) triethoxysilane and The invention relates to at least one of 2-(3-cyclohexenyl)methyldiethoxysilane, the double bond amide monomer is selected from at least one of (Z)-9-octadecenoic acid amide, acrylamide, oleic acid amide, fumaramide, cinnamamide, maleamic acid, erucic acid amide and linoleic acid amide, and the solvent is selected from at least one of water, N,N-dimethylformamide, N,N-dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, chloroform, hexafluoroisopropanol, acetone, butanone, dichloromethane and dimethyl sulfoxide.
[0015] Compared with the prior art, the present invention adopts the above-mentioned raw material selection, wherein the selected initiators cover different chemical properties and reaction conditions, and these initiators can effectively generate free radicals to start polymerization reactions, and are suitable for a variety of polymerization reaction systems; the selected double-bond silane monomers not only introduce silicon elements to improve the heat resistance and chemical stability of the material, but also contain double bonds that can participate in the polymerization reaction, ensuring that they can be evenly integrated into the copolymer chain, thereby enhancing the overall performance of the material; the selected double-bond amide monomers give the material excellent functional properties, such as flexibility, waterproof breathability and biocompatibility, and the presence of amide groups also promotes the formation of hydrogen bonds between molecules, further enhancing the mechanical strength and thermal stability of the material; the selected solvent has good dissolving power, can effectively dissolve each component, ensure the uniformity of the mixed reaction system, and promote sufficient contact and reaction between the monomers.
[0016] In some embodiments, in step S1, the stirring parameters are as follows: temperature is 40-70° C., and time is 5-60 min.
[0017] Compared with the prior art, the present invention adopts the above parameters in that: the temperature range of 40-70°C can ensure that all reactants are fully dissolved and maintain appropriate viscosity so that the components can be mixed more evenly; and the time range of 5-60 minutes is long enough to ensure that the raw materials are thoroughly mixed, but not too long to cause unnecessary energy consumption or the occurrence of side reactions.
[0018] In some embodiments, in step S2, the hydrophobic modifier is selected from one of an organosilicon hydrophobic modifier, a paraffin hydrophobic modifier, or an isocyanate hydrophobic modifier.
[0019] Compared with the prior art, the present invention uses silicone, paraffin or isocyanate hydrophobic modifiers in step S2, which can significantly improve the hydrophobicity and durability of the nanofiber membrane, while giving the material excellent mechanical properties, flexibility and biocompatibility (silicone), achieving cost-effectiveness and environmental friendliness (paraffin), and enhancing the strength and multifunctionality of the material through efficient cross-linking reactions (isocyanate). The selection of these three modifiers not only optimizes the waterproof and breathable performance and application range of the nanofiber membrane, but also ensures the flexibility and economy of the production process, meets the needs of different application scenarios, and thus greatly improves the overall performance and market competitiveness of the product.
[0020] In some embodiments, the concentration of the electrospinning solution is 2-30 wt %.
[0021] Compared with the prior art, the present invention controls the concentration of the electrospinning solution within the above range, which can optimize the fiber formation process and ensure the quality and performance of the nanofiber membrane. A lower concentration (such as 2-10wt%) helps to produce finer and more uniform fibers, which is suitable for preparing ultra-thin and high-porosity nanofiber membranes, suitable for filtration or biomedical applications. Higher concentrations (such as 10-30wt%) can increase the viscosity and stability of the solution, promote the formation of thicker and mechanically stronger fibers, and are suitable for application scenarios that require higher structural integrity and durability. In addition, this concentration range also provides good jet stability and controllability of the electrospinning process, reduces the occurrence of broken wires and bead defects, and ensures consistency in production efficiency and product quality.
[0022] In some embodiments, in step S2, the organic solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, chloroform, hexafluoroisopropanol, acetone, butanone, dichloromethane, and dimethyl sulfoxide.
[0023] Compared with the prior art, the organic solvent used in the present invention has excellent solubility for a variety of polymers and modifiers, and can ensure that the silicon-based acrylonitrile terpolymer and the hydrophobic modifier are fully dissolved to form a uniform and stable spinning solution, especially DMF, NMP and DMSO, which are highly polar aprotic solvents and are suitable for dissolving high molecular weight polymers. By selecting appropriate solvents, the fiber diameter, uniformity and surface morphology can be regulated.
[0024] In some embodiments, in step S2, the mass ratio of the silicon-based acrylonitrile terpolymer, the hydrophobic modifier and the organic solvent is (5-30): (0.5-10): (60-94.5).
[0025] Compared with the prior art, the present invention uses the above-mentioned raw materials in the mass ratio to obtain the spinning solution, which has the following advantages: the polymer content ensures sufficient polymer concentration to form a stable jet, while avoiding excessive concentration leading to excessive solution viscosity or difficulty in jetting, and the content of the hydrophobic modifier can effectively improve the hydrophobicity, waterproof breathability and other specific functions of the nanofiber membrane without affecting the basic properties of the fiber, and the high proportion of organic solvent provides sufficient dissolving capacity to ensure that all components are fully mixed to form a uniform and stable spinning solution. In addition, the wide mass ratio range allows the proportion of each component to be flexibly adjusted according to specific application requirements to meet different performance requirements.
[0026] In some embodiments, in step S3, the specific parameters of the electrospinning method are as follows: voltage control is 5-90 kV, liquid supply rate is 1-10 mL / h, receiving distance is 10-30 cm, winding speed is 40-100 rpm, temperature is 15-30°C, humidity is 30-70%; the thickness of the obtained nanofiber membrane semi-finished product is 10-100 μm.
[0027] Compared with the prior art, the present invention adopts the electrospinning process with the above parameters, and its main functions are: wide range voltage regulation (5-90 kV) provides sufficient electrostatic force to overcome the surface tension of the polymer solution and ensure stable jet formation; moderate liquid supply speed ensures appropriate material supply, and will not cause uneven fiber thickness due to too fast speed, nor affect production efficiency due to too slow speed; reasonable receiving distance ensures that the fibers have enough time to dry and solidify during the flight, while avoiding the problem of fiber dispersion or breakage that may be caused by too long distance; appropriate winding speed helps to evenly distribute the fibers on the receiver, reduces fiber accumulation or gap phenomenon, and improves the overall structural stability and uniformity of the nanofiber membrane; suitable temperature and humidity provide ideal environmental conditions, promote solvent volatilization and fiber solidification, and avoid static electricity problems caused by fiber adhesion due to excessive humidity or too low humidity; precise control of fiber membrane thickness not only provides good mechanical strength, but also ensures excellent functional properties (such as waterproof and breathable).
[0028] In some embodiments, in step S4, the parameters of the pre-oxidation treatment are as follows: temperature is 100-300° C., and time is 0.5-12 h.
[0029] Compared with the prior art, the present invention adopts the above parameters for pre-oxidation treatment, and its advantages are: the present invention adopts high-temperature pre-oxidation technology to transform the internal structure of the fiber membrane, that is, the amide group (CONH2) promotes the cyclization of the silicon-based acrylonitrile ternary copolymer nanofiber, and finally forms a ketocarbonyl (C=O) structure, thereby enhancing its high temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The surface morphology (SEM) of the high temperature resistant fluorine-free waterproof breathable nanofiber membrane prepared in Example 1; Figure 2 This is the contact angle (CA) of the high temperature resistant fluorine-free waterproof and breathable nanofiber membrane prepared in Example 1. DETAILED DESCRIPTION
[0031] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.
[0032] It should be noted that the endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.
[0033] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.
[0034] It is worth mentioning that in the embodiment of the present invention, the high temperature resistant fluorine-free waterproof breathable nanofiber membrane is subjected to index tests according to national standards, as follows: The testing and evaluation of waterproof performance shall refer to GB / T 4744-2013 "Testing and evaluation of waterproof performance of textiles-Hydrostatic pressure method" and GB / T 4745-2012 "Testing and evaluation of waterproof performance of textiles-Water-impregnation method".
[0035] The moisture permeability test refers to GB / T 12704.2-2009 "Test method for moisture permeability of textile fabrics - Part 2: Evaporation method".
[0036] The air permeability test refers to GB / T 5453-1997 "Determination of Air Permeability of Textile Fabrics".
[0037] The mechanical strength test refers to GB / T 3923.1-2013 "Tensile properties of textile fabrics Part 1: Determination of breaking force and elongation at break by strip method".
[0038] The fluorine content test refers to the European standard EN 14582:2016 "Waste characteristics - Halogen and sulfur content - Closed system oxygen combustion and determination method".
[0039] The technical effects of the present invention are described below in conjunction with specific embodiments.
[0040] Example 1 This embodiment provides a preparation method of a high temperature resistant fluorine-free waterproof breathable nanofiber membrane, comprising the following steps: a. Synthesis of silicon-based acrylonitrile terpolymer: a uniformly mixed reaction system containing azobisisobutyronitrile, acrylonitrile, 2-(3-cyclohexenylethyl)triethoxysilane, linoleamide and dimethyl sulfoxide was stirred and reacted at 60°C for 15 min under a nitrogen atmosphere, and a silicon-based acrylonitrile terpolymer was obtained by free radical polymerization, wherein the ratio of acrylonitrile, 2-(3-cyclohexenylethyl)triethoxysilane and linoleamide was 5:4:30, the ratio of azobisisobutyronitrile to acrylonitrile was 0.1%, and the concentration of the mixed solution was 51%; b. Preparation of electrospinning solution: dissolve the silicon-based acrylonitrile terpolymer and the isocyanate hydrophobic modifier in N,N-dimethylformamide in a mass ratio of 5:10:85 and prepare a 15% spinning solution; c. Preparation of nanofiber membrane: The voltage was adjusted to 25 kV, the liquid supply rate was 5 mL / h, the receiving distance was 25 cm, the winding speed was 80 rpm, the temperature was 20°C, and the humidity was 50% to prepare a nanofiber membrane semi-finished product with a thickness of 20 μm; d. The semi-finished nanofiber membrane in c was pre-oxidized at 300°C for 0.5 h to transform the internal structure of the fiber membrane. That is, the amide group (CONH2) promoted the cyclization of the silicon-acrylonitrile ternary copolymer nanofibers, and finally formed a ketocarbonyl (C=O) structure, which further enhanced the hydrophobicity of the nanofiber membrane.
[0041] Example 2 This embodiment provides a preparation method of a high temperature resistant fluorine-free waterproof breathable nanofiber membrane, comprising the following steps: a. Synthesis of silicon-based acrylonitrile terpolymer: a uniformly mixed reaction system including benzoyl peroxide, acrylonitrile, 2,6-octadienyl triethoxysilane, (Z)-9-octadecenoic acid amide and N,N-dimethylformamide was stirred and reacted at 60°C for 15 min under a nitrogen atmosphere, and a silicon-based acrylonitrile terpolymer was obtained through free radical polymerization; wherein the ratio of acrylonitrile, 2,6-octadienyl triethoxysilane and (Z)-9-octadecenoic acid amide was 20:10:10, azobisisobutyronitrile was 1% of acrylonitrile, and the concentration of the mixed solution was 50%; b. Preparation of electrospinning solution: dissolve the silicon-based acrylonitrile terpolymer in step a and silicone-based and paraffin-based hydrophobic modifiers in chloroform at a mass ratio of 20:10:70 and prepare a 30% spinning solution; c. Preparation of nanofiber membrane: The voltage was adjusted to 60 kV, the liquid supply rate was 10 mL / h, the receiving distance was 30 cm, the winding speed was 100 rpm, the temperature was 30°C, and the humidity was 40% to prepare a nanofiber membrane semi-finished product with a thickness of 100 μm; d. The semi-finished nanofiber membrane in c was pre-oxidized at 250 °C for 6 h to transform the internal structure of the fiber membrane. That is, the amide group (CONH2) promoted the cyclization of the silicon-acrylonitrile ternary copolymer nanofibers, and finally formed a ketocarbonyl (C=O) structure, which further enhanced the hydrophobicity of the nanofiber membrane.
[0042] Example 3 This embodiment provides a preparation method of a high temperature resistant fluorine-free waterproof breathable nanofiber membrane, comprising the following steps: a. Synthesis of silicon-based acrylonitrile terpolymer: a uniformly mixed reaction system including initiator ammonium persulfate, acrylonitrile, cis-2-butenyltriethoxysilane, maleamic acid and N-methylpyrrolidone was stirred and reacted at 50°C for 30 min under a nitrogen atmosphere, and a silicon-based acrylonitrile terpolymer was obtained through free radical polymerization; wherein the ratio of acrylonitrile, cis-2-butenyltriethoxysilane and maleamic acid was 15:7:18, azobisisobutyronitrile was 0.5% of acrylonitrile, and the concentration of the mixed solution was 60%; b. Preparation of electrospinning solution: dissolving the silicon-based acrylonitrile terpolymer in a and the organosilicon hydrophobic modifier in tetrahydrofuran in a mass ratio of (5-30): (0.5-10): (60-94.5) to prepare a spinning solution of a certain concentration; c. Preparation of nanofiber membrane: The voltage was adjusted to 75 kV, the liquid supply rate was 6 mL / h, the receiving distance was 15 cm, the winding speed was 50 rpm, the temperature was 15°C, and the humidity was 70% to prepare a nanofiber membrane semi-finished product with a thickness of 50 μm; d. The semi-finished nanofiber membrane in c was pre-oxidized at 180 °C for 12 h to transform the internal structure of the fiber membrane. That is, the amide group (CONH2) promoted the cyclization of the silicon-acrylonitrile ternary copolymer nanofibers, and finally formed a ketocarbonyl (C=O) structure, which further enhanced the hydrophobicity of the nanofiber membrane.
[0043] Comparative Example 1 This comparative example provides a preparation method of an electrospun nanofiber membrane, comprising the following steps: a. Synthesis of silicon-based acrylonitrile terpolymer: a uniformly mixed reaction system containing azobisisobutyronitrile, acrylonitrile, 2-(3-cyclohexenylethyl)triethoxysilane, linoleamide and dimethyl sulfoxide was stirred and reacted at 60°C for 15 min under a nitrogen atmosphere, and a silicon-based acrylonitrile terpolymer was obtained by free radical polymerization, wherein the ratio of acrylonitrile, 2-(3-cyclohexenylethyl)triethoxysilane and linoleamide was 5:4:30, the ratio of azobisisobutyronitrile to acrylonitrile was 0.1%, and the concentration of the mixed solution was 51%; b. Preparation of electrospinning solution: dissolve the silicon-based acrylonitrile terpolymer in a in N, N-dimethylformamide at a mass ratio of 15:85 and prepare a 15% spinning solution; c. Preparation of nanofiber membrane: The voltage was adjusted to 25 kV, the liquid supply rate was 5 mL / h, the receiving distance was 25 cm, the winding speed was 80 rpm, the temperature was 20°C, and the humidity was 50% to prepare a nanofiber membrane with a thickness of 20 μm.
[0044] Comparative Example 2 This comparative example provides a preparation method of an electrospun nanofiber membrane, comprising the following steps: a. Synthesis of silicon-based acrylonitrile terpolymer: A uniformly mixed reaction system containing azobisisobutyronitrile, acrylonitrile, 2-(3-cyclohexenylethyl)triethoxysilane, linoleamide and dimethyl sulfoxide was stirred and reacted at 60°C for 15 minutes under a nitrogen atmosphere, and a silicon-based acrylonitrile terpolymer was obtained by free radical polymerization. Among them, the ratio of acrylonitrile, 2-(3-cyclohexenylethyl)triethoxysilane and linoleamide was 5:4:30, azobisisobutyronitrile was 0.1% of acrylonitrile, and the concentration of the mixed solution was 51%;
[0045] b. Preparation of electrospinning solution: dissolve the silicon-based acrylonitrile terpolymer in a in N, N-dimethylformamide at a mass ratio of 15:85 and prepare a 15% spinning solution; c. Preparation of nanofiber membrane: The voltage was adjusted to 25 kV, the liquid supply rate was 5 mL / h, the receiving distance was 25 cm, the winding speed was 80 rpm, the temperature was 20°C, and the humidity was 50% to prepare a nanofiber membrane semi-finished product with a thickness of 20 μm; d. The semi-finished nanofiber membrane in c was pre-oxidized at 300°C for 0.5 h to transform the internal structure of the fiber membrane. That is, the amide group (CONH2) promoted the cyclization of the silicon-acrylonitrile ternary copolymer nanofibers, and finally formed a ketocarbonyl (C=O) structure, which further enhanced the hydrophobicity of the nanofiber membrane.
[0046] The inventors observed the nanofiber membrane obtained in Example 1. Figure 1 and Figure 2 As shown, Figure 1 The surface morphology (SEM) of the high temperature resistant fluorine-free waterproof breathable nanofiber membrane prepared in Example 1; Figure 1 It can be seen that the nanofiber membrane is formed by randomly stacking nanofibers and there are welding points between adjacent fibers. The membrane has a connected pore structure, which enhances the mechanical properties of the nanofiber membrane. Figure 2 The contact angle (CA) of the high temperature resistant fluorine-free waterproof breathable nanofiber membrane prepared in Example 1 is Figure 2 It can be seen that the hydrophobic angle is as high as 155 o .
[0047] The inventors further performed performance tests on the nanofiber membranes prepared in Examples 1-3 and Comparative Examples 1-2. The test results are shown in Table 1. Table 1 shows the hydrostatic pressure, waterproof grade, air permeability, moisture permeability and mechanical properties test results of the high temperature resistant fluorine-free waterproof and breathable nanofiber membrane prepared in Example 1: Combining the data of Example 1 with that of Comparative Example 1, it can be seen that the pre-oxidation treatment adopted in the present invention will cause a transformation in the internal structure of the fiber membrane, that is, the amide group (CONH2) promotes the cyclization of the silicon-based acrylonitrile ternary copolymer nanofibers, and finally forms a ketocarbonyl (C=O) structure, thereby enhancing its high temperature resistance and waterproof performance.
[0048] Combining the data of Example 1 with that of Comparative Example 2, it can be seen that the use of a hydrophobic modifier in the present invention can significantly improve the hydrophobicity and durability of the nanofiber membrane, while further enhancing the mechanical properties of the obtained nanofiber membrane.
[0049] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A high temperature resistant, fluorine-free, waterproof and breathable nanofiber membrane, characterized in that: The contact angle of the nanofiber membrane is greater than 130° and less than 170°, the pore size is 100-1000 nm, the porosity is 50-95%, the high temperature resistance range is ≤300°C, and the elasticity is 50-200%.
2. The nanofiber membrane according to claim 1, characterized in that The hydrostatic pressure of the nanofiber membrane is 50-150 kPa, the air permeability is 1-20 mm / s, and the moisture permeability is 1-10 4 g / (m 2 24 h), and the waterproof level is >4.
3. A method for preparing a nanofiber membrane according to any one of claims 1 or 2, characterized in that: The preparation method specifically comprises the following steps: S1. Synthesis of silicon-based acrylonitrile terpolymer: mixing raw materials to obtain a mixed reaction system, placing the mixed reaction system under a nitrogen atmosphere, and performing a free radical polymerization reaction under stirring to obtain a silicon-based acrylonitrile terpolymer; S2, preparing an electrospinning solution: dissolving the silicon-based acrylonitrile terpolymer obtained in step S1 and a hydrophobic modifier in an organic solvent to obtain an electrospinning solution; S3, preparing a semi-finished nanofiber membrane: using the electrospinning solution prepared in step S2 as a raw material, an electrospinning method is used to prepare a semi-finished nanofiber membrane; S4, pre-oxidizing the semi-finished nanofiber membrane obtained in step S3 to cyclize the silicon-based acrylonitrile terpolymer to form a ketocarbonyl structure, thereby obtaining a high-temperature resistant, fluorine-free, waterproof and breathable nanofiber membrane.
4. The method for preparing a nanofiber membrane according to claim 3, characterized in that: In the step S1, the raw materials are composed of an initiator, acrylonitrile, a double-bond silane monomer, a double-bond amide monomer and a solvent, and the molar ratio of the acrylonitrile, the double-bond silane monomer and the double-bond amide monomer is (5-20): (0.5-10): (10-30), the mass of the initiator is 0.1-1% of the mass of acrylonitrile, and the concentration of the mixed reaction system is 5-60%.
5. The method for preparing a nanofiber membrane according to claim 3, characterized in that: In the step S1, the initiator is selected from at least one of benzoyl peroxide, tert-butyl peroxide, diisopropyl peroxide, potassium permanganate, ammonium persulfate, and azobisisobutyronitrile, and the double-bond silane monomer is selected from vinyl triethoxysilane, vinyl trimethoxysilane, dimethylethoxy vinyl silane, butyl triethoxysilane, 2,6-octadienyl triethoxysilane, cis-2-butenyl triethoxysilane, 2-(3-cyclohexenylethyl) triethoxysilane, and 2-(3 The invention relates to a method for preparing the present invention wherein the present invention comprises at least one of (Z)-9-octadecenoic acid amide, acrylamide, oleic acid amide, fumaramide, cinnamamide, maleamic acid, erucic acid amide and linoleic acid amide; the solvent is selected from at least one of water, N,N-dimethylformamide, N,N-dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, chloroform, hexafluoroisopropanol, acetone, butanone, dichloromethane and dimethyl sulfoxide.
6. The method for preparing a nanofiber membrane according to claim 3, characterized in that: In step S1, the stirring parameters are as follows: temperature is 40-70° C., and time is 5-60 min.
7. The method for preparing a nanofiber membrane according to claim 3, characterized in that: In the step S2, the hydrophobic modifier is selected from one of an organosilicon hydrophobic modifier, a paraffin hydrophobic modifier or an isocyanate hydrophobic modifier; And / or, the concentration of the electrospinning solution is 2-30wt%.
8. The method for preparing a nanofiber membrane according to claim 3, characterized in that: In step S2, the organic solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, chloroform, hexafluoroisopropanol, acetone, butanone, dichloromethane and dimethyl sulfoxide; And / or, in step S2, the mass ratio of the silicon-based acrylonitrile terpolymer, the hydrophobic modifier and the organic solvent is (5-30): (0.5-10): (60-94.5).
9. The method for preparing a nanofiber membrane according to claim 3, characterized in that: In step S3, the specific parameters of the electrospinning method are as follows: voltage control is 5-90 kV, liquid supply rate is 1-10 mL / h, receiving distance is 10-30 cm, winding speed is 40-100 rpm, temperature is 15-30°C, and humidity is 30-70%; the thickness of the obtained nanofiber membrane semi-finished product is 10-100 μm.
10. The method for preparing a nanofiber membrane according to claim 3, characterized in that: In step S4, the parameters of the pre-oxidation treatment are as follows: temperature is 100-300° C., and time is 0.5-12 h.
Citation Information
Patent Citations
Super-hydrophobic water-proof moisture-permeable nanometer fiber material and preparation method thereof
CN109629113A
Preparation method for fluoride-free waterproof and moisture permeable fibrous membrane with photocatalytic self-cleaning function
CN109881490A
Preparation method of nanofiber membrane material with convertible hydrophilicity and hydrophobicity
CN112323254A
Preparation method of fluorine-free electrostatic spinning waterproof moisture-permeable film based on sulfenyl-alkene photochemical reaction
CN114134702A
Breathable waterproof membrane
CN114619731A